2016
DOI: 10.3390/w8060219
|View full text |Cite
|
Sign up to set email alerts
|

Water Related Health Problems in Central Asia—A Review

Abstract: Abstract:The present paper provides an extensive literature review on water related health issues in Central Asia. Even though the per capita amount of available freshwater is substantial in all Central Asian states the uneven distribution in time and space creates problems for water availability. Due to this, the Central Asian economies are developing under increasing water deficiency. The degradation of water supply systems and sewage treatment plants is often severe leading to potentially high water loss ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 46 publications
0
44
0
Order By: Relevance
“…According to the latest reports from November 2017, Syr Darya River belongs to the second category (moderate pollution). Researchers also found the water of Syr Darya River unfit for agriculture in some places [19][20][21]. They concluded that it is mainly due to the fact that the discharges of waters from densely populated areas of the Ferghana Valley (Uzbekistan, Kyrgyzstan, Tajikistan), and from the lower reaches of the Naryn River to the Kairakkum Dam, directly fall into it.…”
Section: Introductionmentioning
confidence: 99%
“…According to the latest reports from November 2017, Syr Darya River belongs to the second category (moderate pollution). Researchers also found the water of Syr Darya River unfit for agriculture in some places [19][20][21]. They concluded that it is mainly due to the fact that the discharges of waters from densely populated areas of the Ferghana Valley (Uzbekistan, Kyrgyzstan, Tajikistan), and from the lower reaches of the Naryn River to the Kairakkum Dam, directly fall into it.…”
Section: Introductionmentioning
confidence: 99%
“…The Soviet State tried to provide rural people with drinking water and build systems that needed low capital investment and small cost for process equipment but considerably high operational costs [18,19]. The majority of these water supply systems were constructed during the period 1950–1980.…”
Section: Methodsmentioning
confidence: 99%
“…About 70% of developmental problems in the region are caused by freshwater shortages (Severskiy 2004). The main reasons for this are increasing political tensions and worsening ecological and socioeconomic conditions (Bekturganov et al 2016). These facts appear somewhat surprising since the totally renewable water resources (surface and groundwater) of Kazakhstan have been estimated at 100-117 km 3 /year (FAO 2003, GWP 2009, MFA 2016.…”
Section: Introductionmentioning
confidence: 99%